Highly branched PtCu nanodandelion with high activity for oxygen reduction reaction. (1st January 2019) - Yang, Tao; Pukazhselvan, D.; da Silva, E.L.; Santos, Mario C.; Meng, Lijian; Ramasamy, Devaraj; Jothi, Sathiskumar; Graça, Vanessa; Shi, Shikao
Abstract: A facile hydrothermal route has been developed to synthesize the highly branched Pt58 Cu42 nanoparticles via mixing the H2 PtCl6 and CuCl2 with octadecylamine. The Pt58 Cu42 after post treatment forms a dandelion flower 3-D structure. A combination of both the branched shape and PtCu composition effects in the Pt58 Cu42 -nanoparticles shows superior electrocatalytic activity and durability to commercial Pt black for oxygen reduction reaction. The mechanism for the de-alloying and reconstructing of the Pt58 Cu42 -nanoparticles in electrochemical activity and durability tests has been proposed. It is found that after the durability process, the Pt58 Cu42 precursor alloy changes into a substantially Pt enriched PtCu alloy (Pt79 Cu21 ) with a Pt skin. The Pt skin effectively prevents the further dissolution of the Cu below the near-surface to enhance its durability. What's more, the Pt skin exposed to (111) planes which have the lowest surface energy among the low-index planes further promotes the improvement of durability of the PtCu catalyst. Highlights: A novel highly branched PtCu electrode was developed via a facile route. The Pt58 Cu42 after post treatment forms a dandelion flower 3-D structure. It shows superior electrocatalytic activity and durability for ORR. The Pt skin promotes the improvement of durability of the PtCu catalyst.